The Role of the IMF in Overcoming the 1998 Economic Crisis in Indonesia - Ramadania, Siti Fitrah; Tanaijo, Widiyanti; Yusuf, Canda (Economics Monetary Journal, 2026)
The 1998 economic crisis was a major turning point in Indonesia's economic history, marked by a sharp decline in the rupiah exchange rate, a wave of corporate bankruptcies, rising unemployment, and socio-political instability. To address this emergency, the Indonesian government sought financial assistance and a reform program from the International Monetary Fund (IMF). The IMF then disbursed loans with a mandate to implement various reform policies, such as the closure of banks deemed unsound, subsidy cuts, and a comprehensive overhaul of the banking sector. However, this program was not without criticism; some of these policies were deemed to have worsened the living conditions of the lower classes. This study applies qualitative descriptive methods to analyze and explain the IMF's crucial role in overcoming the crisis. The research employs a systematic literature review methodology, analyzing secondary data from peer-reviewed journals, official IMF documents, and government reports published between 1997 and 2024, with thematic content analysis to identify patterns in IMF intervention strategies and their socio-economic impacts. The results show that, although the IMF's interventions succeeded in restoring macroeconomic stability, the implementation of its policies often clashed with Indonesia's social realities. This experience provides valuable lessons for Indonesia regarding the need for strict economic supervision, policies sensitive to social impacts, and the importance of maintaining political stability in the face of crises.